EKSPLORASI MAKNA FASTABIQUL KHAIRAT DALAM TRADISI MAULID NABI DI KAMPUNG KADUBERUK KECAMATAN CIOMAS SERANG BANTEN - Nayla Azzahra; Sulis tiawati; Eka Faradilah; Ina Salmah Febriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Antasari Banjarmasin, 2025)
Abstract: The Maulid Nabi tradition in Kaduberuk Village, Banten Province is a local religious practice that combines cultural values and Islamic teachings through various Islamic competitions that have been held for many years. This activity is not only a celebration but also a means of internalizing Quranic values, especially the concept of fastabiqul khairat or competing in goodness. This study aims to understand the meaning of fastabiqul khairat in this tradition and to see its application in the social and religious life of the community. The study uses a qualitative method with an ethnographic approach through participatory observation, in-depth interviews, and documentation, and is analyzed using the Miles and Huberman model with triangulation validation and member checking. The results show that the value of fastabiqul khairat is reflected in mutual cooperation, community contributions, and active participation in religious competitions. In addition, this tradition has given rise to the practice of Living Qur'an, marked by the assignment of ongoing worship duties to the winners of the competition, such as becoming a muezzin or leader of the marhaban. In conclusion, the Maulid tradition in Kaduberuk Village functions as a collective space that fosters spiritual awareness, social solidarity, and the practice of Quranic teachings in daily life, so that it is not only an annual ritual but also a medium for shaping the religious values of the community. Keywords: Fastabiqul Khairat, Maulid Nabi, Living Qur'an, Religious Traditions, Ethnography